Differences in Eosinophil and Basophil Counts Before and After Administration of Pyrantel Pamoate Among Waste Collection Workers at the Terjun Landfill, Medan Marelan District, Infected with Soil-Transmitted Helminths (STH) - Nazara, Ade; Zahara, Iqrina (Health & Medical Sciences, 2025)
Helminthiasis remains a significant public health concern worldwide. Soil-transmitted helminths (STH) are a group of intestinal parasites transmitted through contaminated soil that can cause infections in humans. Basophils and eosinophils are types of white blood cells that play crucial roles in the immune response against STH infections. When infected with STH, the human body triggers an immune reaction that increases the eosinophil and basophil counts in the bloodstream. To determine the differences in eosinophil and basophil counts before and after the administration of pyrantel pamoate among waste collectors infected with STH at the Terjun Landfill, Medan Marelan District. This study employed a pre-test post-test without control group design to assess changes in eosinophil and basophil counts before and after the administration of pyrantel pamoate. Out of 104 waste collectors who agreed to undergo fecal examination, 35 individuals tested positive for STH infection using the direct smear method. Complete blood count (CBC) tests were performed on these 35 individuals prior to treatment using a hematology analyzer. One week after the administration of pyrantel pamoate, the same individuals underwent repeat CBC testing. Among the 35 STH-infected samples, the mean eosinophil count before treatment was 10.310%, which decreased to 1.085% after treatment. The mean basophil count before treatment was 0.942%, and dropped to 0.000% after treatment. Statistical analysis revealed a significant difference (p < 0.05) in both eosinophil and basophil counts before and after pyrantel pamoate administration. There was a significant difference in eosinophil and basophil counts before and after the administration of pyrantel pamoate among waste collectors infected with STH, indicating that antiparasitic treatment effectively reduced immune response markers associated with STH infection.